Analisis Penggambaran Desain Ilustrasi Makanan pada Webtoon Slice of Life “Mukbang Life” - Magdalena, Elisa; Susanti, Elizabeth (Visualita Jurnal Online Desain Komunikasi Visual, 2024)
Webtoon is a comic that has emerged and is in great demand among young people online in the form of a website that is released continuously following a schedule determined by the licensed comic writer. This research aims to discuss the design of food illustrations in the Webtoon "Mukbang Life" by Hong-kki, based on the true story of an author who likes various delicious foods, especially Korean specialities. The method used in this research is a qualitative descriptive method, which will be explained based on the use of illustration design, color and layout. The results of the research obtained are that using illustration designs designed in detail to describe the author's perception of delicious food can attract the reader's attention and provide clear information through the illustrations used.